Continuous stimulation with differentiation factors is necessary to enhance osteogenic differentiation of human mesenchymal stem cells in-vitro - Reible, Bruno; Schmidmaier, Gerhard; Prokscha, Matthäus; Moghaddam-Alvandi, Arash; Westhauser, Fabian (Growth factors, 2017)
Bone defect treatment belongs to the most challenging fields in orthopedic surgery and requires the well-coordinated application of mesenchymal stem cells (MSC) and differentiation factors. MSC isolated from reaming material (RMSC) and iliac crest (BMSC) in combination with bone morphogenetic protein-7 (BMP-7) and insulin-like growth factor-1 (IGF-1) have been used. The short half-life of both factors limit their applications: a burst release of the factor can probably not induce sustainable differentiation. We stimulated MSC in osteogenic differentiation medium with three different concentrations of BMP-7 or IGF-1: Group A was stimulated continuously, group B for 24 h and group C remained without any stimulation. Osteogenic differentiation was measured after seven and 14 days by alizarin red staining and alkaline phosphatase (ALP) activity. Continuous stimulation led to higher levels of osteogenic differentiation than short-term stimulation. This could lead to a reconsideration of established application forms for differentiation factors, aiming to provide a more sustained release.